Coal gasification furnace nozzle cooling water scale inhibition treatment method

CN122916375APending Publication Date: 2026-10-16张丽梅
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611358400.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0009]为了克服现有技术的上述缺陷,本发明的实施例提供一种粉煤气化炉烧嘴冷却水阻垢处理方法,针对现有烧嘴冷却水阻垢技术中垢在烧嘴冷却盘管内部生成、不同类型垢缺乏差异化调控、析出垢颗粒无法有效排除的技术问题

Benefits of technology

[0043]This invention adjusts the pH to 6.8–7.0 through S1 water quality pre-conditioning, changing the precipitation of calcium carbonate from an explosive to a gradual process, thus avoiding the simultaneous formation of a large number of crystal nuclei that would result in excessively fine particles that are difficult to filter. By adding sodium chloride, the solubility of scale-forming salts in the demineralized water is reduced through the salting-out effect. These two operations together create favorable conditions for the cooling and precipitation of S2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916375A_ABST
    Figure CN122916375A_ABST
Patent Text Reader

Abstract

The application discloses a coal gasification furnace burner cooling water scale inhibition treatment method, and relates to the technical field of coal gasification furnace burner cooling water treatment. The method comprises the following steps: S1, water quality pre-adjustment; S2, three-stage progressive cooling induced precipitation; S3, nano-crystal seed directional implantation; S4, intermittent ultrasonic secondary activation; S5, gradient addition of a shape control agent; S6, dispersion and stabilization treatment; S7, standing and curing and particle size screening; and S8, filtration and water quality recovery. The three-stage progressive cooling makes calcium carbonate scale, magnesium scale and silicon scale sequentially precipitate in respective corresponding temperature windows, and the three kinds of nano-crystal seeds are classified and induced, three kinds of shape control agents are gradient added, and three kinds of dispersion stabilizers are synergistically acted, so that the precipitated scale particles are suspended in water in a loose spherical shape, and are filtered out of the system. The application can reduce the burner cooling coil pressure difference growth rate, and is suitable for scale inhibition treatment of various coal gasification furnace burner cooling water systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pulverized coal gasifier burner cooling water treatment technology, specifically to a method for scale inhibition treatment of pulverized coal gasifier burner cooling water. Background Technology

[0002] The process burner is one of the components of a pulverized coal gasifier. In the pulverized coal gasification process, the burner head operates in a high-temperature environment exceeding 1400℃ within the gasifier furnace. To extend the burner's service life, a burner cooling coil is installed at the burner head, through which demineralized water is circulated for cooling and protection.

[0003] The burner cooling water system uses demineralized water as the cooling medium. Demineralized water from the pipeline system is first sent to the demineralized water storage tank of the gasification unit, pressurized by a water pump, and then sent to the system's existing demineralized water cooler for cooling. It is then distributed in multiple streams to the burner cooling coils of each process burner, with a single burner cooling water flow rate of 12 m³ / h. The demineralized water is heated to 80–120°C in the burner cooling coils, absorbs heat, and returns to the cooling water system. It is then cooled again to 40–45°C by the system's existing demineralized water cooler before being recycled. The demineralized water described in this invention is the circulating medium of the burner cooling water system.

[0004] The core problem faced by burner cooling water systems in actual operation is scaling. During the circulation of demineralized water, the solubility of dissolved calcium, magnesium, and silicon ions in the water changes due to temperature variations, causing them to precipitate and deposit on the inner wall of the burner cooling coil, forming scale. Specifically, calcium carbonate exhibits anomalous solubility characteristics, with its solubility decreasing as temperature increases. On the high-temperature heat exchange surface of the burner cooling coil, calcium bicarbonate decomposes into calcium carbonate, precipitating and adhering to the tube wall to form hard scale. The precipitation tendency of calcium carbonate is significant above 40–45℃; the precipitation rate of magnesium salts accelerates in the temperature range of 35–25℃; and the degree of polymerization of silica increases when the temperature decreases to 15–25℃, precipitating in a colloidal state. The scale layer reduces heat transfer efficiency, leading to decreased cooling effect at the process burner head, increased wall temperature, and increased risk of ablation; in severe cases, it can block cooling channels, causing localized overheating and ablation of the process burner, or even leakage at the weld of the burner cooling coil. Damage to the burner cooling coil is one of the main reasons why the gasifier cannot operate for extended periods.

[0005] Existing scaling treatment technologies for burner cooling water systems involve adding scale inhibitors and dispersants to demineralized water to suppress scale formation through chelation, lattice distortion, and dispersion. However, this method has the following drawbacks:

[0006] First, scale inhibitors work by chemically suppressing scale formation or deposition when it is about to form, which is a passive defense strategy. Scale-forming ions still exist in the demineralized water and may precipitate and deposit under high-temperature conditions after entering the burner cooling coil, failing to fundamentally solve the scaling problem in the burner cooling coil. Scale buildup leads to decreased heat transfer efficiency, increased burner head temperature, and shortened burner cooling coil lifespan.

[0007] Second, existing methods use a single scale inhibitor to treat all scale-forming ions in the water uniformly. Scale in burner cooling water includes various types such as calcium carbonate scale, magnesium scale, and silica scale. The precipitation conditions and crystal morphology of different types of scale are different, making it difficult for a single scale inhibitor to effectively control multiple types of scale at the same time, resulting in limited scale inhibition effect.

[0008] Third, existing methods only focus on inhibiting scale formation, lacking effective means to remove already precipitated scale particles from the system. The precipitated scale particles remain suspended in the demineralized water and circulate with it, and some fine particles may continue to deposit on the burner cooling coil walls. Summary of the Invention

[0009] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a method for scale inhibition treatment of burner cooling water in pulverized coal gasifiers, which addresses the technical problems in the existing burner cooling water scale inhibition technology, such as scale formation inside the burner cooling coil, lack of differentiated control of different types of scale, and inability to effectively remove precipitated scale particles.

[0010] To achieve the above objectives, the present invention provides the following technical solution:

[0011] A method for scale inhibition treatment of burner cooling water in a pulverized coal gasifier includes the following steps:

[0012] S1: Adjust the pH of the demineralized water from the burner cooling water circuit of the pulverized coal gasifier to 6.8-7.0, and add sodium chloride to the demineralized water.

[0013] S2: The demineralized water treated in S1 is sequentially cooled through a first cooling stage, a second cooling stage, and a third cooling stage. The first cooling stage cools the demineralized water to 35°C, the second cooling stage cools it to 25°C, and the third cooling stage cools it to 15°C. In the first cooling stage, calcium carbonate scale in the demineralized water mainly precipitates out; in the second cooling stage, magnesium scale in the demineralized water mainly precipitates out; and in the third cooling stage, silica scale in the demineralized water mainly precipitates out.

[0014] S3: Surface-activated nano-calcium carbonate seed crystals, nano-magnesium carbonate seed crystals, and nano-silica seed crystals are sequentially added to the demineralized water treated in S2. The dosage of the nano-calcium carbonate seed crystals is 3–5 mg / L, the dosage of the nano-magnesium carbonate seed crystals is 2–4 mg / L, and the dosage of the nano-silica seed crystals is 1–3 mg / L.

[0015] S4: Apply intermittent ultrasonic treatment to the desalinated water that has been treated by S3.

[0016] S5: Polyepoxysuccinic acid, sodium polyaspartate, and hydrolyzed polymaleic anhydride are added sequentially to the demineralized water treated in S4, with the concentrations of the three substances decreasing in that order. The concentration of polyepoxysuccinic acid is 8–12 mg / L, the concentration of sodium polyaspartate is 5–8 mg / L, and the concentration of hydrolyzed polymaleic anhydride is 3–5 mg / L.

[0017] S6: Add sodium alginate, sodium carboxymethyl cellulose, and sodium dodecyl sulfate sequentially to the demineralized water treated in S5. The concentration of sodium alginate is 1.5–3.0 mg / L, the concentration of sodium carboxymethyl cellulose is 0.5–1.5 mg / L, and the concentration of sodium dodecyl sulfate is 0.2–0.5 mg / L.

[0018] S7: The demineralized water treated in S6 is allowed to stand at a constant temperature of 15°C. After standing, a concentrated slurry containing scale particles, accounting for 5% of the total volume of the demineralized water in the standing tank, is discharged from the bottom of the standing tank.

[0019] S8: Filter the demineralized water treated in S7 and remove scale particles from the demineralized water. Warm the filtered demineralized water to 40-45°C. Then, add ammonia to the warmed demineralized water to adjust the pH to 7.5-8.5. Next, add sodium gluconate to the pH-adjusted demineralized water. Return the demineralized water treated in the above steps to the pulverized coal gasifier burner cooling water circuit.

[0020] As a further preferred embodiment of the technical solution of the present invention, in step S2, the demineralized water outlet of the third cooling section is used in reverse order as the precooling medium for the second cooling section and the first cooling section.

[0021] As a further preferred embodiment of the technical solution of the present invention, in step S2, the first cooling stage cools the demineralized water from 40-45°C to 35°C, and the residence time of the demineralized water in the first cooling stage is 5-8 minutes; the second cooling stage cools the demineralized water from 35°C to 25°C, and the residence time of the demineralized water in the second cooling stage is 5-8 minutes; the third cooling stage cools the demineralized water from 25°C to 15°C, and the residence time of the demineralized water in the third cooling stage is 5-8 minutes.

[0022] As a further preferred embodiment of the technical solution of the present invention, in step S2, carbon dioxide gas is bubbled into the demineralized water in the third cooling stage, and the carbon dioxide gas is introduced after the demineralized water is cooled to 15°C.

[0023] As a further preferred embodiment of the technical solution of the present invention, in step S3, the nano-calcium carbonate seed crystals, the nano-magnesium carbonate seed crystals, and the nano-silica seed crystals are surface activated by ammonia solution and ultrasonic treatment before addition; the addition interval of each seed crystal is 3 to 5 minutes.

[0024] As a further preferred embodiment of the technical solution of the present invention, in step S4, the intermittent ultrasound treatment is to apply ultrasound for 30 seconds every 5 minutes of operation.

[0025] As a further preferred embodiment of the technical solution of the present invention, in step S7, the settling time is 25 to 35 minutes, and the average particle size of the scale particles increases to 15 to 30 μm; the settling is carried out in a settling tank with a conical bottom.

[0026] As a further preferred embodiment of the technical solution of the present invention, it also includes: backwashing, citric acid solution circulation cleaning, and replenishing surface-activated nanocrystal seeds for the equipment used to achieve each cooling stage in S2 and the settling tank used for settling every 72 hours of operation.

[0027] The working principle of this invention is as follows:

[0028] In the S1 water quality pretreatment step, the pH of the desalinated water is adjusted to 6.8–7.0 to reduce the CO3 content in the desalinated water. 2- Partially converted to HCO3 - Reduce CO3 2- The activity of the sodium chloride is increased, thus changing the precipitation of calcium carbonate during the subsequent cooling process from an explosive to a gradual process, avoiding the simultaneous formation of a large number of crystal nuclei that would result in excessively fine particles that are difficult to filter. The addition of sodium chloride utilizes the salting-out effect to reduce the solubility of scale-forming salts in the demineralized water, creating more favorable thermodynamic conditions for subsequent induced precipitation.

[0029] In the S2 three-stage progressive cooling process, the different solubilities of calcium carbonate, magnesium salts, and silicate in different temperature ranges are utilized. The solubility of calcium carbonate decreases with decreasing temperature, and is relatively low between 40 and 45°C. At 35°C, supersaturation further increases, accelerating the precipitation rate; therefore, the first cooling stage is dominated by calcium carbonate scale precipitation. Magnesium carbonate also exhibits anomalous dissolution behavior, with an accelerated precipitation rate in the 35–25°C temperature range; therefore, the second cooling stage is dominated by magnesium scale precipitation.

[0030] The solubility of silica in water is positively correlated with temperature. When the temperature drops to 15℃, the solubility decreases significantly, and it precipitates in a colloidal state. Therefore, the third cooling stage is dominated by silica scale precipitation. Through the stepwise cooling of three temperature gradients, calcium carbonate scale, magnesium scale, and silica scale are precipitated sequentially within their respective temperature windows.

[0031] In the S3 seed-directed implantation step, the three types of nano-seeds correspond to three types of scale: nano-calcium carbonate seed corresponds to calcium carbonate scale, nano-magnesium carbonate seed corresponds to magnesium scale, and nano-silica seed corresponds to silicon scale.

[0032] The order in which the three types of seed crystals are added corresponds to the precipitation order of the three types of scale in S2: calcium carbonate precipitates first, so nano-calcium carbonate seed crystals are added first; magnesium scale precipitates next, so nano-magnesium carbonate seed crystals are added next; and silicon scale precipitates last, so nano-silica seed crystals are added last. The surface-activated nano-seed crystals provide heterogeneous nucleation sites. The surface activation treatment forms hydroxylated active sites on the seed crystal surface. These active sites can form coordination bonds with calcium and magnesium ions in the demineralized water, lowering the energy barrier for heterogeneous nucleation and causing scale-forming ions to preferentially precipitate on the seed crystal surface rather than deposit on the pipe wall.

[0033] In the secondary activation step of S4 seed crystals, the cavitation effect of low-frequency pulsed ultrasound generates microjets and shock waves, which can remove the scale layer that has formed on the seed crystal surface, thereby exposing fresh active sites, breaking up the tiny scale crystals that have precipitated but have not yet grown, thereby increasing the number of seed crystals, while preventing the agglomeration between seed crystal particles.

[0034] Intermittent operation (applying ultrasound for 30 seconds every 5 minutes) instead of continuous ultrasound is used because continuous ultrasound may cause excessive breakage of the deposited scale particles, which would reduce filtration efficiency; intermittent operation can achieve a balance between removing scale and maintaining particle integrity.

[0035] In the gradient dosing step of the S5 morphology regulator, polyepoxysuccinic acid corresponds to calcium carbonate scale, enabling it to transform from the calcite type to the aragonite type. Sodium polyaspartate corresponds to magnesium scale, chelating calcium, magnesium, and other polyvalent metal ions and altering the calcium salt crystal structure. Hydrolyzed polymaleic anhydride corresponds to silica scale, adsorbing onto the surface of calcium carbonate crystal nuclei, thus charging the nuclei. Due to the repulsion of like charges, the tiny crystals are dispersed into the aqueous solution, while simultaneously dispersing and inhibiting the polymerization of silicic acid.

[0036] The concentrations of the three regulators decrease sequentially, corresponding to the proportions of the three types of scale precipitation (calcium scale accounts for 60-70%, magnesium scale accounts for 15-25%, and silicon scale accounts for 10-15%); the order of addition corresponds to the order of precipitation of the three types of scale.

[0037] In the S6 dispersion stabilization step, sodium alginate adsorbs onto the surface of scale particles through steric hindrance, forming a polymer brush that prevents particle agglomeration. Sodium carboxymethyl cellulose increases the apparent viscosity of the demineralized water, reducing the settling velocity of the particles. Sodium dodecyl sulfate, as an anionic surfactant, adsorbs onto the particle surface, imparting a negative charge to the particles and enhancing their dispersibility through electrostatic repulsion.

[0038] In the S7 settling and maturation step, small-sized scale particles gradually dissolve, and their substances redefine on the surface of large-sized scale particles, making the particle size distribution of scale particles more uniform, with the average particle size increasing to 15-30 μm. The bottom of the settling tank is conical, and large particles sink to the bottom of the cone under gravity. After settling, a concentrated slurry containing scale particles, accounting for 5% of the total volume of demineralized water in the settling tank, is discharged from the bottom of the cone, achieving pre-screening of particle size.

[0039] In the S8 filtration and water restoration process, two-stage filtration traps and removes scale particles from the desalinated water. The water is then heated to 40-45°C to restore the desalinated water temperature to its pre-treatment temperature, preventing thermal shock from the low-temperature desalinated water entering the high-temperature process burners. Ammonia water is then used to adjust the pH to 7.5-8.5, ensuring the desalinated water pH meets the requirements of the burner cooling water system; ammonia water also acts as a corrosion inhibitor. Sodium gluconate further enhances the corrosion protection of the burner cooling coil metal.

[0040] As a further preferred technical solution, in step S2, the demineralized water outlet of the third cooling section is used sequentially as the precooling medium for the second and first cooling sections. Specifically, the demineralized water outlet temperature of the third cooling section at 15°C is first fed into the heat exchanger of the second cooling section as the precooling medium for the second cooling section; after heat exchange in the second cooling section, the demineralized water temperature rises to 25°C and is then fed into the heat exchanger of the first cooling section as the precooling medium for the first cooling section. Chilled water only supplements the cooling capacity shortfall required by the third cooling section, achieving cascaded utilization of cooling capacity.

[0041] As a further preferred technical solution, carbon dioxide gas is bubbled into the demineralized water in the third cooling stage. The carbon dioxide gas is introduced after the demineralized water has cooled to 15°C. After dissolving, the carbon dioxide forms carbonic acid, which forms a soluble bicarbonate complex with the residual calcium and magnesium ions in the demineralized water. This prevents the residual scale-forming ions from precipitating out as hard scale but instead allows them to exist stably in the demineralized water as soluble complexes.

[0042] The technical effects and advantages of this invention are as follows:

[0043] This invention adjusts the pH to 6.8–7.0 through S1 water quality pre-conditioning, changing the precipitation of calcium carbonate from an explosive to a gradual process, thus avoiding the simultaneous formation of a large number of crystal nuclei that would result in excessively fine particles that are difficult to filter. By adding sodium chloride, the solubility of scale-forming salts in the demineralized water is reduced through the salting-out effect. These two operations together create favorable conditions for the cooling and precipitation of S2.

[0044] This invention utilizes a three-stage progressive cooling process (S2) to sequentially precipitate calcium carbonate, magnesium, and silica scale within their respective temperature windows. This achieves differentiated precipitation and treatment of different scale types, solving the problem in existing technologies where a single scale inhibitor cannot effectively control multiple scale types simultaneously. Furthermore, by using the demineralized water from the outlet of the third cooling stage as a pre-cooling medium for both the second and first cooling stages, a cascaded utilization of cooling capacity is achieved. Chilled water is only used to supplement the cooling capacity gap required by the third cooling stage, reducing chilled water consumption.

[0045] This invention achieves the directional precipitation of different types of scale through the classification and sequential addition of three types of nanocrystals (S3). The addition order of the three types of crystals corresponds one-to-one with the precipitation order of the three types of scale. Through the secondary activation treatment of the crystal surface (S4) and the use of intermittent ultrasonic operation, a balance is achieved between removing the scale layer on the crystal surface and maintaining the integrity of the scale particles, thus maintaining its activity at different stages of the crystal life cycle.

[0046] This invention achieves differentiated control of the crystal morphology of different types of scale by gradient addition of three morphology regulators, namely polyepoxysuccinic acid, sodium polyaspartate, and hydrolyzed polymaleic anhydride. The addition concentrations of polyepoxysuccinic acid, sodium polyaspartate, and hydrolyzed polymaleic anhydride decrease sequentially, corresponding to the precipitation ratio of the three types of scale. The addition order corresponds to the precipitation order of the three types of scale. This enables differential control of the crystal morphology of different types of scale, transforming scale particles from layered and needle-like to spherical, thereby reducing the tendency of scale particles to adhere to the wall surface.

[0047] This invention utilizes the synergistic effect of three dispersants (S6), the steric hindrance effect of sodium alginate, the thickening effect of sodium carboxymethyl cellulose, and the electrostatic repulsion of sodium dodecyl sulfate to ensure that the precipitated scale particles remain monodisperse in the demineralized water. Through the static aging process (S7), the scale particles are allowed to grow to a filterable size of 15–30 μm, and a concentrated slurry accounting for 5% of the total volume of demineralized water in the conical settling tank is discharged from the bottom to achieve pre-screening of particle size. Finally, through filtration (S8), the scale particles are trapped and discharged from the system, preventing scale from entering the burner cooling coil and significantly reducing the amount of scale buildup in the burner cooling coil.

[0048] This invention restores the water quality using S8 water, reheats it to 40-45°C, adjusts the pH of the ammonia water to 7.5-8.5, and replenishes it with sodium gluconate corrosion inhibitors, making the treated desalinated water completely compatible with the burner cooling water system, thus achieving zero-interference reuse of the burner cooling water system.

[0049] This invention introduces carbon dioxide gas after the third cooling stage of S2 has finished cooling. This introduction at this time allows the residual scale-forming ions to complex into soluble bicarbonate. If introduced earlier, the residual ions will complex with all the scale-forming ions in the water, which will weaken the precipitation effect of the first two cooling stages. Therefore, this timing design ensures that the residual ions do not undergo secondary precipitation in the subsequent pipeline.

[0050] This invention utilizes online flushing and regeneration, performing backwashing, citric acid solution circulation cleaning, and seed crystal replenishment every 72 hours of operation. This allows the system to operate stably for extended periods without shutdown, making it suitable for continuous industrial applications of pulverized coal gasifier burner cooling water systems. Attached Figure Description

[0051] Figure 1 This is a schematic diagram of the process flow for the scale inhibition treatment method of the burner cooling water in the pulverized coal gasification furnace according to the present invention. Detailed Implementation

[0052] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0053] Preparation of simulated burner cooling water:

[0054] Based on the actual operating water quality data of the pulverized coal gasifier burner cooling water system, simulated burner cooling water was prepared. The simulated water sample was prepared using analytical grade reagents: CaCl2·2H2O was used to prepare Ca... 2+ The stock solution was prepared with MgSO4·7H2O. 2+ For the stock solutions, prepare a SiO2 stock solution using Na2SiO3·9H2O and an alkalinity stock solution using NaHCO3. After mixing the stock solutions in the specified proportions, dilute with deionized water to the target concentration, and adjust the pH to the target value using dilute hydrochloric acid or dilute sodium hydroxide solution.

[0055] The water quality indicators of the simulated water sample are as follows: Ca 2+ Concentration of 200–500 mg / L, Mg 2+ The concentration is 50–150 mg / L, the SiO2 concentration is 10–30 mg / L, the total alkalinity is 150–300 mg / L, the pH is 7.5–8.5, and the temperature is 40–45℃.

[0056] Experimental setup:

[0057] The laboratory simulation apparatus includes: a raw water storage tank, a metering pump, a three-stage tubular cooling reactor (each stage with independent temperature control), a seed crystal addition unit, an ultrasonic treatment unit, a reagent addition unit, a settling tank, a filtration unit, and online monitoring instruments. Each cooling reactor is a jacketed tubular reactor, with circulating water at different temperatures circulated within the jacket for temperature control. The first stage is controlled at 35℃, the second at 25℃, and the third at 15℃.

[0058] The on-site verification was conducted on the bypass of the burner cooling water system of a pulverized coal gasification unit, with a water treatment capacity of 1.0 m³ / h.

[0059] Detection method:

[0060] Ca 2+ The concentration was determined by EDTA complexometric titration (GB / T15452-2009). Mg 2+ The concentration was determined by EDTA complexometric titration, using Eriochrome Black T as an indicator. The total amount of calcium and magnesium was titrated with EDTA standard solution, and then the amount of calcium was subtracted. 2+ Mg was obtained by measurement 2+ The concentration of SiO2 was determined by the silicomolybdenum blue spectrophotometric method (GB / T12149-2017). Turbidity was determined by the turbidimeter method (GB / T13200-1991). The particle size of scale particles was determined by a laser particle size analyzer.

[0061] The following is a detailed description of the operating parameters for each step.

[0062] Detailed operation of S1:

[0063] After the demineralized water enters the pretreatment unit, its pH value is first measured using an online pH meter. When the measured value is higher than 7.0, the hydrochloric acid metering pump is activated to add a 5% (w / w) dilute hydrochloric acid solution to the demineralized water. The amount of hydrochloric acid added is automatically controlled based on feedback from the online pH meter, with a pH control target of 6.8–7.0. When the pH value of the demineralized water is lower than 6.8, no hydrochloric acid is added.

[0064] Sodium chloride is added in solid form, using a dry powder dosing machine to add industrial-grade sodium chloride (purity ≥99%) to the demineralized water. The dosage of sodium chloride is determined based on the conductivity of the demineralized water: when the original conductivity of the demineralized water is ≤200 μS / cm, the dosage is 20 mg / L; when the conductivity is >200 and ≤400 μS / cm, the dosage is 15 mg / L; and when the conductivity is >400 μS / cm, the dosage is 10 mg / L.

[0065] The residence time of desalinated water in the pretreatment unit is controlled by adjusting the opening of the outlet valve of the pretreatment unit, and the residence time is set to 2 to 5 minutes.

[0066] The target pH range is 6.8–7.0. When the pH is below 6.8, increasing the amount of hydrochloric acid may introduce excessive chloride ions; when the pH is above 7.0, CO32-... 2- With high activity, it easily undergoes explosive nucleation during cooling and precipitation, forming fine particulate scale. The sodium chloride dosage is 10–20 mg / L. Dosage below 10 mg / L results in insufficient salting-out effect; dosage above 20 mg / L increases the salinity of the desalinated water, potentially affecting subsequent water quality. The retention time is 2–5 minutes.

[0067] Detailed operation of S2:

[0068] Each of the three cooling sections uses an independent plate heat exchanger for heat exchange and cooling.

[0069] The cold side of the plate heat exchanger in the first cooling section is supplied with demineralized water from the outlet of the second cooling section as a precooling medium. When the temperature of the demineralized water at the outlet of the second cooling section cannot be stably controlled at the target value of 25℃±1℃, supplementary cooling is provided by introducing chilled water at a temperature of 18℃. The outlet temperature of the first cooling section is controlled by adjusting the flow rates of the precooling medium and the supplementary chilled water, with a target temperature of 35℃±1℃.

[0070] The cold side of the plate heat exchanger in the second cooling section is supplied with demineralized water from the outlet of the third cooling section as a precooling medium. When the temperature of the demineralized water at the outlet of the third cooling section cannot be stably controlled at the target value of 15℃±1℃, supplementary cooling is provided by introducing chilled water at a temperature of 8℃. The outlet temperature of the second cooling section is controlled by adjusting the flow rates of the precooling medium and the supplementary chilled water, with a target control temperature of 25℃±1℃.

[0071] Chilled water is introduced into the cold side of the plate heat exchanger in the third cooling section. The chilled water is a 25% ethylene glycol solution with a temperature of -5℃. The outlet temperature of the third cooling section is controlled to be 15℃±1℃ by adjusting the flow rate of the chilled water.

[0072] The residence time of the demineralized water in each cooling section is controlled by adjusting the effective volume of each section of the tubular reactor, with the residence time set to 5–8 minutes. The effective volume of the tubular reactor is equal to the demineralized water volumetric flow rate multiplied by the residence time.

[0073] In the third cooling section, carbon dioxide gas is introduced through microporous aeration discs installed at the end of the tubular reactor. The pore size of the microporous aeration discs is 0.5–2 μm, and they are installed 1 meter before the outlet of the third cooling section. The flow rate of carbon dioxide gas is controlled by a mass flow meter, with an input flow rate of 0.5–1.0 L / (min·m³). 3 The introduction of carbon dioxide gas is initiated after the demineralized water has cooled to 15°C and stabilized for 1 minute.

[0074] The outlet temperature of the first cooling stage is 35℃. Calcium carbonate precipitates rapidly at 35℃; above 35℃, the precipitation is insufficient; below 35℃, some magnesium scale precipitates prematurely, interfering with the segmented precipitation effect. The outlet temperature of the second cooling stage is 25℃. Magnesium scale precipitates rapidly at 25℃; above 25℃, the precipitation is insufficient; below 25℃, some silica scale precipitates prematurely. The outlet temperature of the third cooling stage is 15℃. Silica scale polymerizes and precipitates rapidly at 15℃; above 15℃, the silica scale precipitation is insufficient. The residence time in each stage is 5–8 minutes. The CO2 flow rate is 0.5–1.0 L / (min·m²). 3 ).

[0075] Detailed operation of S3:

[0076] Surface activation was performed in a seed activation tank: nanocrystalline seed powder was added to an ammonia solution with a pH of 9.5, at a mass ratio of 1:50 between the nanocrystalline seed powder and the ammonia solution. Under this pH condition, the seed surface exhibits a high degree of hydroxylation, which is beneficial for the formation of stable active sites. This mass ratio ensures that the seed crystals are fully dispersed in the ammonia solution and that surface activation is complete.

[0077] The seed crystal suspension was placed in an ultrasonic generator with a frequency of 40 kHz and ultrasonically treated for 15 minutes at an ultrasonic power density of 0.5 W / mL. During the ultrasonic treatment, the temperature of the seed crystal suspension was controlled at 25–30 °C using jacket cooling water.

[0078] After ultrasonic treatment, the seed crystal suspension is continuously injected into the demineralized water using a metering pump at a set flow rate. The interval between each seed crystal addition is 3–5 minutes, controlled by adjusting the start time of the metering pump. The amount of each seed crystal added is controlled by adjusting the injection flow rate of the seed crystal suspension.

[0079] The particle size of nano-calcium carbonate seed crystals is 30–80 nm, nano-magnesium carbonate seed crystals are 40–100 nm, and nano-silica seed crystals are 20–60 nm. The dosages of the three seed crystals are 3–5 mg / L, 2–4 mg / L, and 1–3 mg / L, respectively. The interval between seed crystal additions is 3–5 minutes. The pH of the ammonia solution is 9.5. The ultrasonic treatment frequency is 40 kHz, and the time is 15 minutes.

[0080] Detailed operation of S4:

[0081] The ultrasonic probe is a rod-shaped structure, inserted into the center of the pipe along the flow direction of the demineralized water. The ultrasonic frequency is 28 kHz, and it operates intermittently: ultrasound is applied for 30 seconds every 5 minutes. The power density of the ultrasonic treatment is 0.3–0.5 W / mL. The ultrasonic probe is installed 5–10 meters downstream of the S3 seed crystal addition point to ensure that the seed crystals are fully dispersed in the demineralized water before secondary activation.

[0082] In S3, 40kHz ultrasound is used for pre-activation of the seed crystals, while in S4, 28kHz ultrasound is used for online secondary activation. The two frequencies differ because: 40kHz ultrasound acts on the mixture of seed crystal powder and ammonia solution, mainly to promote surface chemical reactions and seed crystal dispersion; while 28kHz ultrasound acts on the flowing demineralized water system, with a lower frequency and stronger cavitation effect, making it suitable for online removal of scale from the surface of the seed crystal-scale particle composite.

[0083] Detailed operation of S5:

[0084] Polyepoxysuccinic acid, sodium aspartate, and hydrolyzed polymaleic anhydride were all added as 10% (w / w) aqueous solutions. The interval between each reagent addition was 3–5 minutes, controlled by adjusting the start-up time of the metering pump. The dosage of each reagent was controlled by adjusting the speed of the metering pump.

[0085] The dosage concentration of PESA is 8–12 mg / L, the dosage concentration of PASP is 5–8 mg / L, and the dosage concentration of HPMA is 3–5 mg / L.

[0086] Detailed instructions for using S6:

[0087] Sodium alginate and sodium carboxymethyl cellulose were added as a 0.5% (w / w) aqueous solution, while sodium dodecyl sulfate was added as a 1% (w / w) aqueous solution. The addition interval for each dispersant stabilizer was 3–5 minutes, controlled by adjusting the start-up time of the metering pump. The dosage of each dispersant stabilizer was controlled by adjusting the speed of the metering pump.

[0088] The dosage concentrations of sodium alginate, CMC, and SDS are 1.5–3.0 mg / L, 0.5–1.5 mg / L, and 0.2–0.5 mg / L, respectively.

[0089] Detailed instructions for using S7:

[0090] The effective volume of the settling tank is calculated based on the demineralized water flow rate and the set settling time (25-35 minutes). The settling tank is equipped with a jacket, through which constant-temperature circulating water at 15℃ is circulated to maintain the demineralized water temperature inside the tank at a constant 15℃±1℃.

[0091] The settling tank has a 60-degree cone angle at the bottom, which ensures that scale particles slide smoothly to the bottom of the cone under gravity. A slag discharge pipe is located at the bottom of the cone. After settling, first open the slag discharge pipe valve at the bottom of the cone to discharge the concentrated slurry, which accounts for 5% of the total volume of demineralized water in the settling tank. After slag discharge, close the slag discharge pipe valve and send the supernatant in the tank to the next process.

[0092] The settling temperature is 15℃, and the settling time is 25–35 minutes. The bottom slag discharge ratio is 5% of the total volume of demineralized water in the settling tank.

[0093] Detailed instructions for using S8:

[0094] The two-stage filtration system uses bag filters. The primary filter has a filtration accuracy of 50μm, and the filter bag is made of polypropylene. The secondary filter has a filtration accuracy of 5–10μm, and the filter bag is made of polyester.

[0095] The filtered demineralized water is reheated using a plate heat exchanger. Warm water at 40–45°C is introduced to the hot side of the plate heat exchanger, while the filtered demineralized water is introduced to the cold side. The outlet temperature of the demineralized water is controlled to be 40–45°C by adjusting the flow rate of the warm water.

[0096] Ammonia solution was added at a concentration of 5% (w / w), with the dosage controlled by an online pH meter, and the target pH was 7.5–8.5. Sodium gluconate was added as a 5% (w / w) aqueous solution, with a concentration of 1–2 mg / L based on the effective ingredient.

[0097] The primary filtration accuracy is 50μm, and the secondary filtration accuracy is 5–10μm. The recovery temperature is 40–45℃. The target pH adjustment value is 7.5–8.5. The ammonia dosage should not exceed 2 mg / L. The sodium gluconate dosage is 1–2 mg / L.

[0098] Detailed instructions for using S9:

[0099] During the backwashing process, close the inlet and outlet valves of each cooling section and settling tank, open the backwash inlet valve and backwash drain valve, and backwash the clear liquid stored in the clear water tank after S8 filtration. The backwash flow rate is 1.5 times the normal operating flow rate, the backwash time is 10 minutes, and the backwash drain is discharged into the wastewater collection tank.

[0100] In the citric acid solution circulation cleaning step, each cooling section and the settling tank are rinsed with a 0.5% (w / w) citric acid solution for 15 minutes. During the circulation cleaning process, the temperature of the citric acid solution is controlled at 40–50°C. After circulation cleaning, the water is rinsed with clean water until the pH of the discharged water is 6.5–7.5.

[0101] In the seed addition step, surface-activated nano-seeds are added at 30% of the initial addition amount in S3. The addition ratio of the three types of seed is the same as the initial addition ratio.

[0102] The backwashing and regeneration cycle is 72 hours, an optimal value determined experimentally. During this cycle, the system pressure differential remains stable, and the effluent parameters meet requirements. The backwash flow rate is 1.5 times the normal flow rate, and the time is 10 minutes. The citric acid concentration is 0.5%, the cleaning time is 15 minutes, and the cleaning temperature is 40–50°C. The seed crystal replenishment ratio is 30% of the initial dosage.

[0103] Example

[0104] Example 1

[0105] like Figure 1 As shown, this embodiment is implemented on the burner cooling water system of a pulverized coal gasification unit. The burner cooling water system uses demineralized water as the cooling medium, the system has a water processing capacity of 12 m³ / h, and the temperature of the demineralized water returning from the burner cooling water circuit is 42°C.

[0106] S1: Demineralized water from the pulverized coal gasifier burner cooling water circuit is introduced into the pretreatment unit. The pH of the demineralized water is measured to be 7.8. Hydrochloric acid is added to the demineralized water to adjust the pH to 6.9. Simultaneously, sodium chloride is added to the demineralized water at a dosage of 15 mg / L. The demineralized water remains in the pretreatment unit for 3 minutes.

[0107] S2: The demineralized water treated in S1 is sequentially cooled through a first cooling section, a second cooling section, and a third cooling section. In the first cooling section, the demineralized water is cooled from 42℃ to 35℃, with a residence time of 6 minutes. In the second cooling section, the demineralized water is cooled from 35℃ to 25℃, with a residence time of 6 minutes. In the third cooling section, the demineralized water is cooled from 25℃ to 15℃, with a residence time of 6 minutes. The demineralized water exiting the third cooling section is used as the precooling medium for both the second and first cooling sections in reverse order. In the third cooling section, after the demineralized water reaches 15℃, carbon dioxide gas is bubbled into it at a flow rate of 0.8 L / (min·m³). 3 ).

[0108] S3: Surface-activated nano-calcium carbonate seed crystals, nano-magnesium carbonate seed crystals, and nano-silica seed crystals are sequentially added to the desalinated water treated in S2. The dosage of nano-calcium carbonate seed crystals is 4 mg / L, the dosage of nano-magnesium carbonate seed crystals is 3 mg / L, and the dosage of nano-silica seed crystals is 2 mg / L.

[0109] The surface activation treatment methods for the three types of nanocrystals were as follows: the nanocrystals were dispersed in an ammonia solution with a pH of 9.5, and subjected to ultrasonic treatment at a frequency of 40 kHz for 15 minutes with an ultrasonic power density of 0.5 W / mL. The order of addition of the three types of nanocrystals was as follows: first, nano-calcium carbonate crystals were added, followed by nano-magnesium carbonate crystals after a 4-minute interval, and then nano-silica crystals after another 4-minute interval.

[0110] S4: After S3 is completed, intermittent low-frequency pulse ultrasound treatment at a frequency of 28kHz is applied to the desalinated water treated by S3, with ultrasound applied for 30 seconds every 5 minutes.

[0111] S5: Polyepoxysuccinic acid, sodium polyaspartate, and hydrolyzed polymaleic anhydride are added sequentially to the desalinated water treated in S4. The concentration of polyepoxysuccinic acid is 10 mg / L, the concentration of sodium polyaspartate is 6 mg / L, and the concentration of hydrolyzed polymaleic anhydride is 4 mg / L. The order of addition of the three speciation regulators is as follows: first, add polyepoxysuccinic acid; after a 4-minute stand, add sodium polyaspartate; after another 4-minute stand, add hydrolyzed polymaleic anhydride.

[0112] S6: Add sodium alginate, sodium carboxymethyl cellulose, and sodium dodecyl sulfate sequentially to the demineralized water treated in S5. The concentration of sodium alginate is 2.0 mg / L, the concentration of sodium carboxymethyl cellulose is 1.0 mg / L, and the concentration of sodium dodecyl sulfate is 0.3 mg / L. The order of addition of the three dispersants and stabilizers is as follows: first add sodium alginate, wait 4 minutes, then add sodium carboxymethyl cellulose, wait another 4 minutes, and then add sodium dodecyl sulfate.

[0113] S7: The demineralized water treated in S6 is transferred to a settling tank with a conical bottom and settling at a constant temperature of 15°C for 30 minutes. After settling, 5% of the concentrated slurry, which is the total volume of the demineralized water in the settling tank, is discharged from the bottom of the settling tank.

[0114] S8: The demineralized water treated in S7 is sent to a two-stage filtration system for filtration. The first-stage filtration has a filtration accuracy of 50 μm, and the second-stage filtration has a filtration accuracy of 8 μm. The resulting demineralized water is then reheated to 42°C using a plate heat exchanger.

[0115] Ammonia water was added to the rehydrated demineralized water to adjust the pH to 8.0, with an ammonia water dosage of 1.5 mg / L. Sodium gluconate was then added to the pH-adjusted demineralized water at a concentration of 1.5 mg / L. The demineralized water treated in the above manner was then returned to the pulverized coal gasifier burner cooling water circuit.

[0116] S9: Every 72 hours of operation, perform an online backwash and regeneration process on the equipment used for each cooling stage in S2 and the settling tank used in S7. The backwash flow rate is 1.5 times the normal operating flow rate, and the backwash time is 10 minutes. Circulate and rinse with a 0.5% citric acid solution for 15 minutes, then rinse with clean water until neutral. Supplement with 30% of the initial dosage in S3 using surface-activated nanocrystals.

[0117] Example 2

[0118] The difference between this embodiment and Embodiment 1 lies in the different process parameters.

[0119] In S1, the initial pH of the deionized water was 8.2. Hydrochloric acid was added to adjust the pH to 7.0, the sodium chloride dosage was 20 mg / L, and the residence time was 5 minutes.

[0120] In section S2, the first cooling stage cools the demineralized water from 45℃ to 35℃ for 8 minutes; the second cooling stage cools the demineralized water from 35℃ to 25℃ for 8 minutes; and the third cooling stage cools the demineralized water from 25℃ to 15℃ for 8 minutes. The carbon dioxide gas flow rate is 1.0 L / (min·m³). 3 ).

[0121] In S3, the dosage of nano-calcium carbonate seed crystals is 5 mg / L, the dosage of nano-magnesium carbonate seed crystals is 4 mg / L, and the dosage of nano-silica seed crystals is 3 mg / L. The interval between the addition of each seed crystal is 5 minutes.

[0122] In S5, the concentration of polyepoxysuccinic acid is 12 mg / L, the concentration of sodium polyaspartate is 8 mg / L, and the concentration of hydrolyzed polymaleic anhydride is 5 mg / L.

[0123] In S6, the concentration of sodium alginate is 3.0 mg / L, the concentration of sodium carboxymethyl cellulose is 1.5 mg / L, and the concentration of sodium dodecyl sulfate is 0.5 mg / L.

[0124] In S7, the settling time is 35 minutes.

[0125] In S8, the filtration accuracy of the secondary filter is 5μm, the temperature is restored to 45℃, the pH of the ammonia water is adjusted to 8.5, and the sodium gluconate dosage is 2mg / L.

[0126] The remaining steps are the same as in Example 1.

[0127] Example 3

[0128] The difference between this embodiment and Embodiment 1 lies in the different process parameters.

[0129] In S1, the initial pH of the deionized water was 7.5. Hydrochloric acid was added to adjust the pH to 6.8, the sodium chloride dosage was 10 mg / L, and the residence time was 2 minutes.

[0130] In section S2, the first cooling stage cools the demineralized water from 40℃ to 35℃ for 5 minutes; the second cooling stage cools the demineralized water from 35℃ to 25℃ for 5 minutes; and the third cooling stage cools the demineralized water from 25℃ to 15℃ for 5 minutes. The carbon dioxide gas flow rate is 0.5 L / (min·m). 3 ).

[0131] In S3, the dosage of nano-calcium carbonate seed crystals is 3 mg / L, the dosage of nano-magnesium carbonate seed crystals is 2 mg / L, and the dosage of nano-silica seed crystals is 1 mg / L. The interval between the addition of each seed crystal is 3 minutes.

[0132] In S5, the concentration of polyepoxysuccinic acid is 8 mg / L, the concentration of sodium polyaspartate is 5 mg / L, and the concentration of hydrolyzed polymaleic anhydride is 3 mg / L.

[0133] In S6, the concentration of sodium alginate is 1.5 mg / L, the concentration of sodium carboxymethyl cellulose is 0.5 mg / L, and the concentration of sodium dodecyl sulfate is 0.2 mg / L.

[0134] In S7, the settling time is 25 minutes.

[0135] In S8, the filtration accuracy of the secondary filter is 10μm, the temperature is restored to 40℃, the pH of the ammonia water is adjusted to 7.5, and the sodium gluconate dosage is 1mg / L.

[0136] The remaining steps are the same as in Example 1.

[0137] Comparative Example

[0138] No pH adjustment was performed on any of the comparative examples, and the detection methods for each comparative example were the same as those in the examples.

[0139] Comparative Example 1

[0140] Using the same simulated burner cooling water quality as in Example 1, Ca 2+ The concentration is 320 mg / L, Mg 2+ The concentration was 85 mg / L, the SiO2 concentration was 22 mg / L, the pH was 7.8, and the temperature was 42℃. Polyepoxysuccinic acid (PESA) was added to the simulated water at a concentration of 10 mg / L, and the mixture was stirred for 30 minutes at a constant temperature of 42℃. The water was then filtered and the effluent quality was measured. Comparative Example 1 only used the single scale inhibitor PESA at room temperature without any cooling treatment or the addition of seed crystals or other agents.

[0141] Comparative Example 2

[0142] The same simulated burner cooling water quality as in Example 1 was used. The simulated water was directly cooled from 42°C to 15°C, allowed to stand at a constant temperature of 15°C for 30 minutes, and then filtered to determine the quality of the effluent.

[0143] Comparative Example 3

[0144] The same simulated burner cooling water quality and the same three-stage cooling steps and seed crystal addition steps as in Example 1 were used, but the morphology modifier in S5 was not added. The remaining steps were the same as in Example 1.

[0145] Comparative Example 4

[0146] The same simulated burner cooling water quality and the same three-stage cooling steps and morphology modifier addition steps as in Example 1 were used, but the nano-seeds in S3 were not added. The remaining steps were the same as in Example 1.

[0147] Comparative Example 5

[0148] The same simulated burner cooling water quality and the same three-stage cooling steps as in Example 1 were used. However, all the reagents in S3, S4, S5, and S6 (nano-calcium carbonate seed crystals, nano-magnesium carbonate seed crystals, nano-silica seed crystals, polyepoxysuccinic acid, sodium polyaspartate, hydrolyzed polymaleic anhydride, sodium alginate, sodium carboxymethyl cellulose, and sodium dodecyl sulfate) were mixed and added at once after the cooling was completed. The total amount added was the same as in Example 1, and the settling and filtration steps were the same as in Example 1.

[0149] Comparison of processing results:

[0150] The treatment effects of each embodiment and comparative example are compared in Table 1. Embodiment 1 and Comparative Examples 1-5 were all tested under the condition that the total hardness of the influent was 320 mg / L; Embodiment 2 had a total hardness of 280 mg / L influent, and Embodiment 3 had a total hardness of 350 mg / L influent.

[0151] Table 1 Comparison of processing effects of each embodiment and comparative example

[0152] As can be seen from Table 1:

[0153] First, among the comparative examples, the Ca content of Comparative Example 1 (conventional scale inhibitor method) was... 2+ The removal rate was only 23%, Mg 2+ The removal rate was 18%, and the SiO2 removal rate was 9%, both significantly lower than those in the examples. Comparative Example 2 (single cooling treatment) showed some removal effect, but Ca... 2+ The removal rate was only 38%, significantly lower than in the previous examples. This indicates that neither conventional scale inhibitor methods nor simple cooling treatments can effectively remove scale-forming ions.

[0154] Second, the Ca in Comparative Example 3 (three-stage cooling + seeding, no morphology modifier) 2+ The removal rate was 58%, compared to Comparative Example 4 (three-stage cooling + morphology modifier, no seed crystals) for Ca. 2+ The removal rate was 52%, which is lower than the 72% in Example 1. This indicates that the optimal removal effect can only be achieved through the synergistic effect of both seed crystals and morphology modifiers, and the absence of either step leads to a significant decrease in the removal rate.

[0155] Third, in comparison example 5 (all reagents were mixed and added at once), Ca... 2+The removal rate was 48%, lower than 72% in Example 1. This indicates that the order and timing of agent addition have a significant impact on the treatment effect. Adding the agents sequentially according to the order specified in this invention can fully leverage the synergistic effect of each agent.

[0156] Fourth, among the three embodiments, Embodiment 2 had the highest removal rate (Ca). 2+ The removal rate of 75% was related to the low hardness of the influent (280 mg / L); the influent hardness of Example 3 was the highest (350 mg / L), and the removal rate was relatively low (Ca). 2+ The removal rate was 68%, but still within an acceptable range. The total hardness of the effluent in all embodiments was reduced to below 102 mg / L, meeting the water quality requirements of the burner cooling water system.

[0157] In the field verification of Example 1, the changes in the pressure difference between the inlet and outlet of the burner cooling coil were continuously recorded. The pressure difference of the burner cooling coil refers to the pressure difference between the inlet and outlet of the burner cooling coil, which directly reflects the degree of scaling on the inner wall of the burner cooling coil. The results are shown in Table 2.

[0158] Table 2 Comparison of Burner Cooling Coil Pressure Difference Changes

[0159] As shown in Table 2, the rate of increase in differential pressure in the burner cooling coil was significantly reduced after treatment using the method of the present invention. Before treatment, the differential pressure increased from 120 kPa to 280 kPa within 12 months, while after treatment, it only increased from 120 kPa to 148 kPa within 12 months, indicating that the method of the present invention effectively inhibited the deposition of scale in the burner cooling coil.

[0160] In the field verification of Example 1, the changes in the inlet and outlet pressure difference of the treatment system (cooling section and settling tank) of the present invention were recorded simultaneously. This pressure difference reflects the operating status of the treatment system itself. Records were made every 30 days, and the results are shown in Table 3.

[0161] Table 3 Pressure difference changes in the processing system of this invention

[0162] As can be seen from Table 3, during the six months of continuous operation, the pressure difference of the treatment system of the present invention slowly increased from 122 kPa to 131 kPa, with an average monthly pressure difference increase of 1.5 kPa / month, indicating that the treatment system is operating stably.

[0163] With other process parameters kept the same as in Example 1, the effect of the total cooling time in S2 on the treatment effect was investigated. The results are shown in Table 4.

[0164] Table 4. Effects of different total cooling times on treatment effectiveness

[0165] As shown in Table 4, when the total cooling time was extended from 12 minutes to 18 minutes, the removal rate of each ion significantly improved; however, when the time was further extended to 24 minutes and 30 minutes, the removal rate no longer increased significantly. Therefore, the preferred residence time for each stage is 5–8 minutes, and the preferred total cooling time is 15–24 minutes.

[0166] With other process parameters kept the same as in Example 1, the effect of the total dosage of the three types of nanocrystals in S3 on the treatment effect was investigated. The results are shown in Table 5.

[0167] Table 5. Effect of Total Seed Addition Amount on Treatment Efficacy

[0168] Table 5 shows that the removal rate is lowest when the total seed crystal dosage is 0. As the seed crystal dosage increases, the removal rate of each ion gradually increases. When the total dosage reaches 9 mg / L, the removal rate is close to its maximum value. Therefore, the preferred total seed crystal dosage is 6–9 mg / L.

[0169] With other process parameters kept the same as in Example 1, the effects of different addition sequences of the three types of regulators in S5 on the treatment effect were investigated. The results are shown in Table 6.

[0170] Table 6. Effects of the order of addition of different forms of regulators on the treatment effect

[0171] As shown in Table 6, the removal rate of each ion was highest when added in the order of "PESA→PASP→HPMA" according to the present invention. When the addition order was changed or when they were added simultaneously, the removal rate decreased.

[0172] In the field verification of Example 1, the system was run continuously for 6 months, and samples were taken every 30 days to measure the total hardness and turbidity of the effluent. The results are shown in Table 7.

[0173] Table 7 Long-term operational stability data

[0174] As can be seen from Table 7, during the continuous operation for 6 months, the total hardness of the effluent remained stable in the range of 85 to 91 mg / L, and the turbidity of the effluent remained stable in the range of 0.7 to 0.8 NTU, indicating that the method of the present invention has good long-term operational stability.

[0175] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for scale inhibition treatment of burner cooling water in a pulverized coal gasification furnace, characterized in that, Includes the following steps: S1: Adjust the pH of the demineralized water from the burner cooling water circuit of the pulverized coal gasifier to 6.8-7.0, and add sodium chloride to the demineralized water; S2: The demineralized water treated in S1 is sequentially cooled through a first cooling section, a second cooling section, and a third cooling section. The first cooling section cools the demineralized water to 35°C, the second cooling section cools it to 25°C, and the third cooling section cools it to 15°C. In the first cooling section, calcium carbonate scale in the demineralized water mainly precipitates out. In the second cooling section, magnesium scale in the demineralized water mainly precipitates out. In the third cooling section, silica scale in the demineralized water mainly precipitates out. S3: Surface-activated nano-calcium carbonate seed crystals, nano-magnesium carbonate seed crystals, and nano-silica seed crystals are sequentially added to the demineralized water treated by S2; the amount of nano-calcium carbonate seed crystals added is 3-5 mg / L, the amount of nano-magnesium carbonate seed crystals added is 2-4 mg / L, and the amount of nano-silica seed crystals added is 1-3 mg / L. S4: Apply intermittent ultrasonic treatment to the desalinated water treated by S3; S5: Polyepoxysuccinic acid, sodium polyaspartate, and hydrolyzed polymaleic anhydride are added sequentially to the desalinated water treated by S4, with the concentrations of the three substances decreasing in that order; the concentration of polyepoxysuccinic acid is 8-12 mg / L, the concentration of sodium polyaspartate is 5-8 mg / L, and the concentration of hydrolyzed polymaleic anhydride is 3-5 mg / L. S6: Add sodium alginate, sodium carboxymethyl cellulose, and sodium dodecyl sulfate sequentially to the demineralized water treated in S5; the concentration of sodium alginate is 1.5–3.0 mg / L, the concentration of sodium carboxymethyl cellulose is 0.5–1.5 mg / L, and the concentration of sodium dodecyl sulfate is 0.2–0.5 mg / L. S7: The demineralized water treated by S6 is allowed to stand at a constant temperature of 15℃; after standing, a concentrated slurry containing scale particles, accounting for 5% of the total volume of demineralized water in the standing tank, is discharged from the bottom of the standing tank. S8: Filter the demineralized water treated in S7 and remove scale particles from the demineralized water; warm the obtained demineralized water to 40-45℃; then add ammonia water to the warmed demineralized water to adjust the pH to 7.5-8.5; then add sodium gluconate to the demineralized water after pH adjustment; and send the demineralized water treated in the above way back to the pulverized coal gasifier burner cooling water circuit.

2. The method according to claim 1, characterized in that, In step S2, the demineralized water from the outlet of the third cooling section is used in reverse order as the precooling medium for the second cooling section and the first cooling section.

3. The method according to claim 1, characterized in that, In step S2, the first cooling stage cools the demineralized water from 40-45°C to 35°C, and the residence time of the demineralized water in the first cooling stage is 5-8 minutes; the second cooling stage cools the demineralized water from 35°C to 25°C, and the residence time of the demineralized water in the second cooling stage is 5-8 minutes; the third cooling stage cools the demineralized water from 25°C to 15°C, and the residence time of the demineralized water in the third cooling stage is 5-8 minutes.

4. The method according to claim 3, characterized in that, In step S2, carbon dioxide gas is bubbled into the demineralized water in the third cooling section. The carbon dioxide gas is introduced after the demineralized water has cooled to 15°C.

5. The method according to claim 1, characterized in that, In step S3, the nano-calcium carbonate seed crystals, the nano-magnesium carbonate seed crystals, and the nano-silica seed crystals are surface activated by ammonia solution and ultrasonic treatment before addition; the addition interval of each seed crystal is 3 to 5 minutes.

6. The method according to claim 5, characterized in that, In S4, the intermittent ultrasound treatment involves applying ultrasound for 30 seconds every 5 minutes of operation.

7. The method according to claim 5, characterized in that, In step S7, the settling time is 25 to 35 minutes, during which the average particle size of the scale particles increases to 15 to 30 μm; the settling is carried out in a settling tank with a conical bottom.

8. The method according to claim 1, characterized in that, Also includes: Every 72 hours of operation, the equipment used to achieve each cooling stage in S2 and the settling tanks used for settling are backwashed, cleaned with citric acid solution circulation, and replenished with surface-activated nanocrystal seeds.